Skills Requirements for Business Intelligence, Business Analytics, Big Data Analytics, and Data Science: An Analysis of South African Professionals - Kusena, Adelade (Department of Information Systems, 2023)
This study aimed at investigating the requisite skills and their overlaps for Business Intelligence (BI), Business Analytics (BA), Big Data Analytics (BDA), and Data Science (DS) professionals in South Africa. Studies on benefits, challenges, and concepts on BI and Analytics have been conducted, but few contributions have been made on requisite skills for BI, BA, BDA, and DS. A multi-method approach was adopted using firstly online job advertisement analysis followed by the Delphi technique. A total of 482 online job advertisements were collected for analysis by using LinkedIn and Indeed.com. Descriptive analysis was used to analyze data from online job advertisements. Thematic analysis was used for the categorization of skills. For the Delphi technique, the final number of data professionals were 21 (7 experts from BI, 7 from BA/BDA and 7 from DS). Findings show that data professionals are required to have skills in programming languages such as SQL, Python, R, and Java, specifically for BA, BDA, and DS. They are required to be holders of a degree in Information Systems (IS) or Computer Science or Engineering. The significant skills categories which were shown as needed across all the domains were Data manipulation and processing (Manipulate data using SQL, Transform data from different sources and load it to extract insights (ETL), Formulate validation strategies and methods to ensure accurate and reliable data, Ensure correct data and error handling, Perform data analysis and validation, Soft skills (Communicate effectively, verbally and in writing, Exhibit time management skills, Prioritize workload and work well under pressure, Demonstrate problem-solving skills, Demonstrate excellent analytical skills, Be able to work independently, Apply creativity and innovation), Designing and Coding (Apply agile development processes to achieve outstanding data solutions, Perform data modelling with SQL), and Reporting (Extract insights and trends from data). This study contributes to descriptive knowledge by providing insight into BI, BA, BDA, and DS requisite skills in South Africa.